2009
DOI: 10.1093/carcin/bgp233
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 is induced via EGFR activation and mediates resistance to anoikis-like cell death under lipid rafts/caveolae-disrupting stress

Abstract: The plasma membrane microdomains, lipid rafts, are involved in regulation of cellular functions such as cell survival and adhesion. Cholesterol is a critical component of lipid rafts in terms of their integrity and functions and rafts disruption by cholesterol depletion can induce detachment-induced cell death. Hypoxia inducible factor-1 (HIF-1) alpha is stabilized in hypoxia and transactivates numerous genes required for cellular adaptation to hypoxia. It is also induced by non-hypoxic stimuli and contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…(44). Although lipid-mediated regulation of HIF1-α represents an untapped research area, there exists one report which suggests that changes in membrane properties can modulate HIF1-α expression by affecting EGFR function (45). This raises the possibility that accumulation of lipids may hamper the function of membrane proteins that are positive regulators of HIF1-α expression.…”
Section: Discussionmentioning
confidence: 99%
“…(44). Although lipid-mediated regulation of HIF1-α represents an untapped research area, there exists one report which suggests that changes in membrane properties can modulate HIF1-α expression by affecting EGFR function (45). This raises the possibility that accumulation of lipids may hamper the function of membrane proteins that are positive regulators of HIF1-α expression.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hypoxia on integrin biology could explain why it could protect cells against anoıkis (Rohwer et al, 2008;Lee et al, 2009) and contribute to cancer invasion and metastasis (Sullivan and Graham, 2007).…”
Section: Functional Consequencesmentioning
confidence: 99%
“…Data from prostate cancer animal models have shown that raising or lowering cholesterol, a critical component of rafts [81,82], led to tumor growth promotion or inhibition, respectively [83,84]. Lipid raft cholesterol regulates apoptotic cell death in prostate cancer cells, through epidermal growth factor receptor (EGFR)-mediated Akt and extracellular signal-regulated kinase (ERK) pathways [85].…”
Section: Lipid Rafts In Cancermentioning
confidence: 99%